The Video Gamer Persona: A Five Factor Study Exploring Personality Elements of The Video Gamer - Bean, Anthony; Pooran, Natasha (Journal of Psychology and Psychotherapy Research, 2022)
This research explored personality traits of video gamers utilizing the Big Five Inventory (BFI) totaling 19,416 video gamer participants across seven genres of video game play. The purpose was to uncover personality differences among the different preferred genres of video gamers. Different personality profiles were explored by employing t-tests and multivariate analysis of variance (MANOVA). Mapping of the BFI elements of video gamers across video game genres was conducted using latent profile analysis (LPA) to identify video gamer personality profiles, personality formations across preferred genres of play, examine the pattern of relationships among the variables, and to determine whether different personalities gravitate to specific genres of play. Results found four distinct and different personality profiles: Introversive, Extroversive, Secure Ambiversive, and Insecure Ambiversive; indicated no support for the different classification of video gamers possessing statistically different personality traits (i.e. causal, regular, hardcore); or different genres of video game play did have different personality types playing each genre. As such, evidence is provided for different personalities gravitating towards different genres of play and Carl Jung’s (1921) idea of the introversion/extroversion continuum. Limitations observed were some findings becoming statistically significant with small effect sizes and the BFI possibly not being nuanced enough to detect smaller personality traits. Strengths were the large participant base, generalizability of the study to the video gamer population, and this study providing a basis for personality playing a role in virtual worlds.